Circular RNAs as Competing Endogenous RNAs in Cardiovascular and Cerebrovascular Diseases: Molecular Mechanisms and Clinical Implications - Min, Xue; Liu, Dong-liang; Xiong, Xing-dong (Frontiers in Cardiovascular Medicine, 2021)
Circular RNAs (circRNAs) represent a novel class of widespread and diverse endogenous RNA molecules. This unusual class of RNA species is generated by a back-splicing event of exons or introns, resulting in a covalently closed circRNA molecule. Accumulating evidence indicates that circRNA plays an important role in the biological functions of a network of competing endogenous RNA (ceRNA). CircRNAs can competitively bind to miRNAs and abolish the suppressive effect of miRNAs on target RNAs, thus regulating gene expression at the transcriptional level. The role of circRNAs as ceRNAs in the pathogenesis of cardiovascular and cerebrovascular diseases (CVDs) has been recently reported and highlighted. Understanding the underlying molecular mechanism could aid the discovery of therapeutic targets or strategies against CVDs. Here, we review the progress in studying the role of circRNAs as ceRNAs in CVDs, with emphasis on the molecular mechanism, and discuss future directions and possible clinical implications.